Single straddle carrier routing problem in port container terminals: mathematical model and solving approaches. (1st January 2012) - Ndiaye, Babacar Mbaye; Le Thi, Hoai An; Pham Dinh, Tao
This paper treats the problem of routing straddle carriers during the loading operations of export containers. The straddle carrier (SC) travel distance will be much longer if two consecutive containers must be collected far from one another instead of from consecutive yard-bays. So, finding the minimum straddle carrier travel distance will guarantee port efficiency and allow cost savings. Our objective is to minimise the total travel distance of a straddle carrier. A SC performs a so called partial tour to pick-up containers of a same group, according to the work schedule. This problem is formulated as a mixed-integer linear programming problem, which is hard to solve optimally. In this paper, we reformulate the problem, thanks to exact penalty techniques in DC programming, as a continuous polyhedral DC programme. A combination of the local algorithm DCA and a global optimisation approach based on cutting plane techniques is proposed. Our algorithm, consisting in solving a finite number of linear programmes, converges to a global solution. Computational experiments indicate its efficiency.